Nouveaux Horizons = New Horizons = Neue Horizonte = Nuevos Horizontes = Nieuwe Horizonten - CRAC Alsace, Altkirch (Altkirch : CRAC (Centre Rhenan d'Art Contemporain) Alsace Altkirch, 2006)
Barré, Virginie ; Bourdarel, Katia ; Chevallier, Martin Le ; Declercq, Alain ; Dellsperger, Brice ; Discrit, Julien ; Grasso, Laurent ; Hahn, Clarisse ; Huet, Elodie ; Jeannes, Patrick ; Labaume, Vincent ; Marchetti, Corinne ; Meste, Philippe ; Mréjen, Valérie ; Peinado, Bruno ; Perrin, Frank ; Rigobert, Fabien ; Sacquin, Amandine ; Serralongue, Bruno
ALTK 06I1 A : tekst, ALTK 06I1 B : zw/w ill.
biog., ind. tent., gr. tent. p. 70-81
Duits
Engels
Frans
Nederlands
Keywords: Frankrijk